SEPSIS - EMERGENCY AND DIAGNOSTIC CHALLENGE IN OUT-HOSPITAL CONDITIONS - Vukićević, Verica; Ilic, Andrijana; Obradovic, Aleksandra; Milivojcevic Bevc, Ivana (Halo 194 Scientific Journal of Emergency Medicine, 2025)
Introduction/goal. Sepsis, by definition, is a life-threatening organ dysfunction caused by an inadequate response to infection. Earlier recognition and treatment improves outcome. The aim of the paper is to present a patient in whom the initial pre-hospital examination was suspected, and the diagnosis of sepsis was confirmed in hospital conditions, in order to draw attention to the symptomatology that patients can show in the case of sepsis. Case presentation. A patient suspected of having sepsis is shown. He was initially cared for in the field, with monitoring of vital parameters and adequate therapy, transported to an on-call health facility, where the diagnosis of sepsis was confirmed. Conclusion. Timely recognition and treatment is the key to the survival of patients suffering from sepsis. If the treatment is carried out in the first hour from the onset of symptoms, the survival rate is over 80%, after six hours - only 30%.